Wait no more: How the administration of VAT refunds impacts firm behaviour - Giacomo Brusco; Marlies Piek; Tejaswi Velayudhan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Refunds are an essential feature of well-functioning VAT systems and take up a sizeable portion of government spending. In South Africa, refunds amount to 50 per cent of gross VAT collection, representing a substantial transfer from the government to taxpayers that has to occur at relatively high frequency, often monthly. We show that delays in these refund payments reduce domestic investment, especially by small firms. We use administrative data to provide extensive evidence that firms respond to incentives created by delays and denials of refunds. We exploit a change in the attitude towards refunds of the South African Revenue Authority to quantify these effects via an event study. We find that approximately halving the audit rates of refund-claiming returns and speeding up their processing increased investment by 31 per cent and output by 24 per cent.
Keywords: H21; H25; H83; 330; VAT collection; VAT refunds; event study